Access to dental care among 15-64 year old people - Faezeh Eslamipour; Kamal Heydari; Marzieh Ghaiour; Hoda Salehi (Wolters Kluwer Medknow Publications, 2018)
Introduction: The current study aims to study people's access to oral and dental health-care services and their satisfaction with the services provided to them. Materials and Methods: A descriptive study with multi-stage sampling was conducted on 1360 people aged 16-64 years residing in Isfahan city, Iran. The required data were collected by a questionnaire which comprised of three main parts: demographic characteristics, patients' access to oral and dental health-care services and its barriers and participants' satisfaction with access to services. Data were analyzed by SPSS statistical software. Results: The results showed 40% of participants reported an average level for oral health, and 82% of them did not have any problems regarding access to dental care facilities. The main causes of their dissatisfaction were high cost of services (60%) and insufficient health insurance coverage (40%). About 73% reported that they had to spend 30 min or less to access to a dental health-care facility. In addition, 50% of participants were satisfied with the provided services. The main reported reasons for referring to dentists were oral and dental problems (69%) and regular check-ups (15%). There was no significant relationship between participants' gender, education level, insurance coverage, and access to dental health-care centers (P > 0.05). Conclusion: Most participants were satisfied with access to dental healthcare, but they were dissatisfied with the costs and inadequate insurance coverage. About half of the participants were satisfied with the services provided to them, and the highest level of satisfaction was reported for easy access to health-care centers.